Faktor-Faktor Yang Mempengaruhi Minat Pegawai Negeri Sipil Untuk Melakukan Tindakan Whistleblowing - Refaoni Aida Aida; Herlina Helmy; Mia Angelina Setiawan (Universitas Negeri Padang, 2019)
This study aims to examine the influence of organizational commitment, seriousness of wrongdoing, personal cost and attitude on the whistleblowing intentions among civil servant in the Padang State University. This research used primary data collected from questionnaire survey.Using a sample of 146 respondents, this research show that two determinants significantly affect whistleblowing intention. The two affecting determinants are organizational commitment and seriousness of wrongdoing, and the two not affecting are personal cost and attitude on the whistleblowing intention. The first variable is organizational commitment has significant positive effect on the whistleblowing intentions, where the tcount 3,058> ttable 1,97693at sig0,000 <α 0,05. The second variable is seriousness of wrongdoing has significant positive effect on the whistleblowing intentions, where the tcount 3.347>ttable 1,97693 at sig 0,001 < α 0,05. The third variable is personal cost has not significant positive effect on the whistleblowing intentions, where the tcount 0,573 < ttable1,97693 at sig 0,568 >α 0,05. The last variable is attitude has not significant positive effect om the whistleblowing intentions, where the tcount 0,467 < ttable1,97693 at sig 0,641 > 0,05.